La estimulación temprana y su incidencia en el desarrollo de la grafomotricidad de los niños y niñas de primer año de educación básica de la escuela “oriente ecuatoriano” de la ciudad de nueva Loja. Periodo 2014-2015 - Ninfa Silvana, Cantincuz Rodríguez (2015)
This research was part of an analytical, descriptive and explanatory study of "THE EARLY STIMULATION AND ITS IMPACT ON THE DEVELOPMENT OF GRAFOMOTRICIDAD OF CHILDREN FIRST YEAR OF BASIC EDUCATION SCHOOL " ECUATORIANO EAST OF THE CITY OF NUEVA LOJA. PERIOD 2014-2015", the same that was developed according to the Regulation of Academic System of the National University of Loja. The overall objective raised was: Educate teachers and parents about importance of early stimulation for development in children graphomotor First-Year Basic Education. Scientific, Inductive, Deductive, Analytic-Synthetic, Descriptive and Statistical Model: methods were used. The techniques and instruments used were: The Survey aimed at teachers of the first year of Basic Education School "Ecuadorian Oriente", to identify the Early Learning Activities in daily work; and an Observation applied to children First-Year Basic Education of the Joint Tax School "Ecuadorian Oriente" City of Nueva Loja, to assess the Development of GRAFOMOTRICIDAD. Analyzed the results of the survey of teachers it is concluded that: The results of the survey to teachers concluded that: 100% of teachers surveyed report that their activities to encourage children are: Games, Children's Literature , Puppet, Grafoplásticas Technical and Artistic Expression. The early stimulation helps the process of formation of brain structure, providing adequate incentives to enable it to achieve development with many possibilities. According to the results of the observation guide concludes that: 58% of boys and girls have investigated development GRAFOMOTRICIDAD Highly Satisfactory, 34% and 8% Satisfactory Unsatisfactory.